Craniofacial Flash: Minimizing Radiation Dose in Pediatric Craniofacial Computed Tomography. Issue 7 (October 2018) - Stewart, Neil M.; Hallac, Rami R.; Chou, Pang-Yun; Koral, Korgun; Blackburn, Tim; Kane, Alex A.; Seaward, James R.
Abstract : Background and Purpose: The routine use of computed tomography (CT) in evaluation of pediatric craniofacial abnormalities is controversial. While there are benefits to preoperative imaging, there are risks related to ionizing radiation and sedation/anesthesia. In this study, the authors describe their experience with a new craniofacial CT protocol (Craniofacial-Flash) that provides bone detail equivalent to conventional CT, while delivering a substantially lower radiation dose and reducing the scan time to obviate the requirement of sedation/anesthesia. Methods: Following IRB approval, dose identification and image analysis were conducted retrospectively on all patients who underwent craniofacial CT using either the conventional protocol or Craniofacial-Flash protocol between November 2013 and September 2015. Image analysis consisted of automated segmentation of bone and soft tissue, followed by noise interpretation of each study segment. Results: The conventional CT group included 175 patients (mean age 6.38 years) with a median dose length product of 243.00 mGy·cm. The Craniofacial-Flash CT group included 208 patients (mean age 3.31 years) with median dose length product of 27.60 mGy·cm. Image quality was equivalent for bone, with coefficient of variation values of 0.20 for the conventional CT group and 0.21 for the Craniofacial-Flash group. Soft tissues coefficients of variation were disparate at 0.07 for conventional CT and 0.14 for Craniofacial-Flash protocol. Conclusion: The Craniofacial-Flash protocol reliably generates craniofacial bone images adequate for routine use in craniofacial practice, while reducing the radiation dose by 88.87% compared with a conventional craniofacial CT scan, and eliminating the need for sedation.